2018
DOI: 10.5713/ajas.17.0252
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for temperament in Jeju crossbred horses

Abstract: ObjectiveTemperament can be defined as a type of behavioral tendency that appears in a relatively stable manner in responses to various external stimuli over time. The aim of this study was to estimate genetic parameters for the records of temperament testing that are used to improve the temperament of Jeju crossbred (Jeju×Thoroughbred) horses.MethodsThis study was conducted using 205 horses (101 females and 104 males) produced between 2010 and 2015. The experimental animals were imprinted and tamed according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, the Jeju crossbreds may have attenuated the vigilant traits in Thoroughbreds, which was identified in the present study. Kim et al revealed that the gentleness, patience, and aggressiveness, patience, and aggressiveness had moderate heritabilities, and that sensitivity had a high heritability in the temperament of Jeju crossbred horses [ 10 ]. So, selected breeding for appropriate temperament would be effective for optimal utility in this breed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Jeju crossbreds may have attenuated the vigilant traits in Thoroughbreds, which was identified in the present study. Kim et al revealed that the gentleness, patience, and aggressiveness, patience, and aggressiveness had moderate heritabilities, and that sensitivity had a high heritability in the temperament of Jeju crossbred horses [ 10 ]. So, selected breeding for appropriate temperament would be effective for optimal utility in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…In Jeju (a native Korean pony) crossbred horse (Jeju horse × Thoroughbred), which is one of the subject horse breeds, several reports explored the genetic basis of temperament, with the estimation of genetic parameters, and genetic correlations between temperament traits [ 9 , 10 ]. However, relationships between behavior, physiological responses, and temperament, have not been studied in this breed.…”
Section: Introductionmentioning
confidence: 99%
“…The JH, which is found only in the Jeju island of Korea, is a small-sized hardy horse (Supplemental Figure S1). On average, it has a wither height of ~122 cm, which is shorter than those of the average MH (~140 cm), PZ (~148 cm), and TB horses (~154 cm) 6,7,11,1618 . JH are gentle, hardy, and of a healthy constitution, and are resistant to diseases and stress derived from the harsh environment they live in 3 .…”
Section: Introductionmentioning
confidence: 88%
“…Temperament may have been selected divergently between breeds (even indirectly), and this fact may have altered the distribution of the number of facial whorls of the different breeds/populations, with consequent changes in the variance components [ 27 ]. Breed is known to have a great influence on horse behavior [ 65 ], and behavioral and temperament traits in horses have low to moderate heritability [ 65 , 66 , 67 ]. Thus, hair whorl traits could potentially be used for indirect temperament selection.…”
Section: Discussionmentioning
confidence: 99%